The Influence of Association on Changes in Student Learning Behavior at SMA Negeri 6 Pekanbaru - Vonny Claudia; Gimin Gimin; Supentri Supentri (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research was written against the backdrop of the existence of a phenomenon of changes in student learning behavior caused by the association of students at SMA Negeri 6 Pekanbaru. Changes in learning behavior such as students skipping study, unplugging, smoking, not paying attention to the teacher while studying and others. Based on this phenomenon, the authors are interested in conducting research with the aim of finding out whether there is social influence on changes in student learning behavior at SMA Negeri 6 Pekanbaru. The location of this research was conducted at SMA Negeri 6 Pekanbaru. The research method used is quantitative with data collection techniques, namely questionnaires (questionnaire), observation, interviews and documentation. Based on the results of statistical calculations, Tcount (12.782) Ttable (2.012) means that Ha is accepted. Based on the results of the linear regression equation, the equation is Y = -3.895 + 1.138X, meaning that if association (X) increases by 1, then changes in learning behavior (Y) increase by 1.138. So it can be concluded from the results of the T test that there is an influence of variable X on variable Y, meaning that Ha is accepted, namely: there is an influence on changes in student learning behavior at SMA Negeri 6 Pekanbaru.